Language Maintenanceand The Preservation of Ethnic Identity: A Case of Malay Muslims in Southern Thailand - Kama, Nonglaksana; Yamirudeng, Munirah (Journal of Islam in Asia (E-ISSN 2289-8077), 2012)
Language is known to have an effect on ethnic identity.For cultural groups who hold knowledge of ethnic language as a core value, language shift can lead to a loss of ethnic identity, cultural fragmentation and “non-authentic” expressions of ethnicity Thelanguage has played and is still playing a symbolic role in the evolution and maintenance of ethnic identity within the Malay Muslim community in southern Thailand. Itis significant to know how the Malay language was used as a symbol to create and sustain the Malay identity on the ways in which Malay Muslims today understand ethnic identity, and how ethnic language fits into their own ethnic self-identifications.This paper attempts to answer the question why Malay language constitutes a vital element in the maintenance of Malay ethnic identity among the Malays of southern Thailand.Two facts have been identified regarding the language and ethnicity link among Malay Muslims. First, Malay language is seen as a relevant ethno-cultural marker and its usage is limited within family, relatives and close friends. Second, Malay language is preserved along with Thai language, making many Malay Muslims bilingual, which is quite typical in the southern border provinces of Thailand.